Podcast “English PodClass” sebagai Inovasi Media Pembelajaran untuk Meningkatkan Kemampuan Berbicara dan Menyimak pada Mata Pelajaran Bahasa Inggris - Yusuf, Nuraini; Nur Eva Yanti; Sella Mawarni; Maenuddin Bustanil Syah; Ragil (LOSARI DIGITAL, 2025)
This community engagement project aimed to design and develop a podcast-based instructional medium entitled English PodClass to enhance senior high school students’ speaking and listening competencies in the English language subject. The implementation comprised three major phases: design, production, and dissemination. The design phase involved instructional design activities, including the development of podcast concepts and learning content aligned with the needs of twelfth-grade students at SMA Negeri 8 Makassar, focusing on Hortatory Exposition Text and Discussion Text materials with contextual themes such as Netiquette, Media Literacy, and Climate Change. The production phase encompassed audio recording and post-production processes utilizing Audacity and Adobe Audition software. The final product consisted of three podcast episodes, each lasting 10–15 minutes, organized into introductory, main discussion, and closing segments. The dissemination phase was conducted through digital learning platforms such as YouTube and Google, complemented by online outreach strategies. The project resulted in an educational podcast serving as an innovative, flexible, and engaging instructional medium for English language learning.